Analisis Ketersediaan Koleksi Fiksi dan Tingkat Minat Kunjung Siswa di Perpustakaan SMA Ksatrya 51 Jakarta - Ario Adi Prakoso; Nadya Risky Amanda; Aya Yahya Maulana; Heri Samtani (Universitas Sebelas Maret Library, 2026)
Libraries, as centers of relevant information, provide various types of collections that can be utilized by patrons, including fiction collections. Fiction collections in libraries not only serve to expand knowledge and increase reading interest but also serve as a source of entertainment. This highlights the role of libraries as a recreational resource for their users. Therefore, school libraries should provide fiction collections in addition to textbooks. The presence of fiction collections in school libraries is expected to encourage an increase in student visitation. This study aims to analyze the availability of fiction collections and the level of student visitation at Ksatrya 51 High School Library in Jakarta. This study employs a quantitative method with a descriptive approach. Data analysis involves descriptive statistics, including calculations of means, percentages, and frequency distributions using IBM SPSS version 22 software. Data were collected via a questionnaire distributed to 86 respondents using probability sampling, specifically simple random sampling. The results indicate a mutually supportive relationship between the availability of fiction collections and patrons’ interest in visiting the library, where diverse and high-quality collections can increase user interest, and are supported by a conducive library environment that reinforces the decision to visit.